Oxford english for careers: Medicine: teacher's resource book - McCarter, S. Sam (Oxford English for Careers, 2017)
Medicine is ideal for pre-work students, studying at upper-intermediate to advanced level, who will need to use English in work situations. It is also suitable for doctors and other health professionals who plan to work in English-speaking countries. Medicine develops the vocabulary, language, and skills that students need to read and understand medical texts, to be successful in medical exams, and to communicate effectively and accurately with patients and colleagues.